“Look, I Have Been Working”: Professional Personalization and Gender Negotiation of Women Politicians on Instagram - Eriyanto (Women, Education, and Social Welfare, 2026)
This study examines how Indonesian women members of parliament visualize their political identity through personalization strategies on Instagram. The study employs quantitative content analysis. The research population includes all Instagram posts of women members of the House of Representatives (DPR) for the 2024–2029 term who maintain active and publicly accessible accounts. A total of 98 women legislators have active official Instagram accounts. The unit of analysis consists of single-photo or carousel posts published during the first six months following their inauguration (1 October 2024–31 March 2025). From a total of 5,486 posts, a sample of 1,002 posts was selected using proportional stratified sampling based on each party’s posting distribution. The findings indicate a strong dominance of professional personalization through documentation of official activities and representations of personal qualities as active and competent politicians. Private and emotional personalization are present but appear in relatively smaller proportions, suggesting that these elements are used selectively by women politicians. Meanwhile, intellectual personalization (the articulation of policy positions and ideas) is the least frequently observed dimension.  This pattern suggests that women politicians primarily use social media to construct legitimacy through an image of work performance while simultaneously negotiating gender expectations. However, the dominance of activity-based representation without accompanying expressions of substantive ideas may reinforce a form of political visibility centered on performance rather than policy articulation.